European public policies about the digitalization of the financial sector and the analysis of procedural stages - Rus, Mihaela; Tasențe, Tănase; Sandu, Mihaela Luminița; Nicolae, Nicoleta Lavinia (Technium Social Sciences Journal, 2022)
This study seeks to point out the idea that the purpose of the analysis is to consider public policies related to elements that influence the development in a certain way. The future of the finances is digital: consumers and enterprises have begun to call on digital financial services. The market’s creative participants use new technology, and existing business are changing. Digital funding helps citizens and enterprises resist to unprecedented situations due to COVID-19 pandemic, for example, online authentication allows people to open accounts and to use many services from distance. Increasing proportion of in-store payments is presently digital, and electronic trade has increased dramatically. Ensuring a safe and reliable activity of digital infrastructure is also thanks to the increasing number of online financial services users and to financial sector employee which works on their own from distance. If there are any doubts, now is clear that digital funding could bring benefits, and citizens alongside European enterprises are ready to receive it. Europe must take advantage of this on its recovery activity to repair the damage caused by the pandemic. Digital technology will be essential for new releases. This would help Europe to become a global digital player. The European financial sector can create many projects in all Member States and may play a leading role in areas like digital payment technology. This would bring huge benefits to both consumers and enterprising.